2016
DOI: 10.1111/petr.12742
|View full text |Cite
|
Sign up to set email alerts
|

A quality improvement initiative to increase pneumococcal vaccination coverage among children after kidney transplant

Abstract: Pneumococcal vaccination rates among children receiving a kidney transplant remain suboptimal. Current practice guidelines in the United States recommend giving the 23-valent pneumococcal polysaccharide vaccine (PPSV23) after priming with the 13-valent pneumococcal conjugate vaccine (PCV13). We conducted a quality improvement initiative to increase pneumococcal vaccine rates in our kidney transplant recipients by developing an age-based vaccine algorithm, obtaining vaccine records, and generating reminders for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…The oldest study was published in 2010, and the most recent study was published in 2018. Two of the studies were designed as quasi-experimental interventions,33,34 while three other studies were randomized controlled trials (RCTs) 3537Table 2General characteristics of included studiesSource, author, year, countryParticipants (age range)Type of studiesSample size (n)InterventionDurationOutcomesResultsEffectConclusionChristina Freier et al, 2010, GermanyAdolescents following transplantation (15–19 years)Randomized controlled trialIGR (26) CGr (24)Educational programme using the OTIS system24 monthsprocess outcome (IRK and IRB)clinical outcome (GFR)Overall IRK improved significantly over time ( p <0.0001) for IGr patients relative to CGr.…”
Section: Resultsmentioning
confidence: 99%
“…The oldest study was published in 2010, and the most recent study was published in 2018. Two of the studies were designed as quasi-experimental interventions,33,34 while three other studies were randomized controlled trials (RCTs) 3537Table 2General characteristics of included studiesSource, author, year, countryParticipants (age range)Type of studiesSample size (n)InterventionDurationOutcomesResultsEffectConclusionChristina Freier et al, 2010, GermanyAdolescents following transplantation (15–19 years)Randomized controlled trialIGR (26) CGr (24)Educational programme using the OTIS system24 monthsprocess outcome (IRK and IRB)clinical outcome (GFR)Overall IRK improved significantly over time ( p <0.0001) for IGr patients relative to CGr.…”
Section: Resultsmentioning
confidence: 99%
“…34,35 Others focused on immunization coverage. [36][37][38][39][40] The electronic databases search yielded nine publications. Manual search of the reference list of eligible publication yielded an additional two publications.…”
Section: Resultsmentioning
confidence: 99%
“…For example, QI models have leveraged process changes to prompt compliance such as using point-of-care prompts and algorithms, or teaching QI principles to caregivers for application to local workflows where improvements are needed. [22][23][24][25][26] For example, Gilkey et al showed that education with assessment and feedback in a localized QI intervention for HPV vaccination improved vaccination rates, while also emphasizing the need for further implementation research. 26 Building on that observation, the current study demonstrates that longitudinal community-based QI interventions paired with CME can be associated with enhanced vaccination rates.…”
Section: Discussionmentioning
confidence: 99%